Barium titanate coated nickel powder and powder slurry

By setting the inner shell of an oxygen compound or sulfur compound and the outer shell of barium titanate on the surface of the nickel powder, the barium titanate coated nickel powder with a double-shell structure is solved, and the co-firedness and electrical properties of MLCC are improved.

CN119501064APending Publication Date: 2025-02-25JIANGSU BOQIAN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411850112.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the production process of multi-layer ceramic capacitors (MLCCs), the nickel electrode is prone to oxidation, resulting in a decrease in conductivity, and the nickel slurry shrinks during the firing process and causes warping and fracture.

Method used

A double-shell structure powder with barium titanate coated with nickel powder is used to provide an inner shell of oxygen or sulfur compounds on the surface of the nickel powder, and then a barium titanate shell is provided on the outer layer of the inner shell to improve the bonding and stability of the nickel powder and the dielectric material.

Benefits of technology

Through the double-layer structure of the inner shell and outer shell, the co-firing and binding force of nickel powder and dielectric material are improved, the stability of nickel powder in the firing process is improved, and the yield and electrical properties of MLCC are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119501064A_ABST
    Figure CN119501064A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal powder materials, and particularly relates to barium titanate coated nickel powder and powder slurry, the barium titanate coated nickel powder has a nickel powder core with the specific surface area equivalent particle size d of 30-600nm; the surface has a double-shell structure, an inner shell layer is an oxygen compound and / or a sulfur compound, and an outer shell layer is barium titanate. The barium titanate coated nickel powder disclosed by the invention has a double-shell structure, and besides the advantage that the co-firing property of the nickel powder and a dielectric material is improved through the barium titanate shell of the outer shell, the combination degree of nickel and the dielectric material can be better improved through the oxygen compound and / or the sulfur compound of the inner shell; therefore, the yield of the nickel powder and the dielectric material in the process of preparing the electronic component is improved, and the electrical property of the electronic component is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal powder materials, and in particular relates to barium titanate-coated nickel powder and powder slurry. Background Art

[0002] As the degree of miniaturization of electronic products continues to increase, electronic components are gradually moving towards miniaturization. The advantages of chip components such as small size, light weight, easy assembly and high reliability have also greatly improved the performance of electronic products.

[0003] Multilayer ceramic capacitors (MLCCs) are one of the most important chip passive devices in the modern electronics industry. They are known as the rice of the electronics industry and are widely used in consumer electronics, industrial electronics and modern military electronics. Traditional MLCC internal electrodes use precious metals such as silver and palladium. In addition to being expensive, their high-temperature co-firing, high resistivity and high melting point physical and chemical properties also affect their application in industrial devices. After entering the 1990s, nickel, as a base metal with good physical and chemical properties, has been widely used in MLCC internal electrodes.

[0004] Nickel is a high melting point metal that is not easily oxidized. When co-fired with the dielectric barium titanate at high temperatures, it will not be seriously oxidized, volatilized, or lost. When co-fired with the dielectric, it will not diffuse into the dielectric to affect the electrical insulation of the dielectric material. It also has many characteristics such as easy size control and good dispersibility. However, when nickel powder is used alone in the MLCC production process, the following problems still exist: nickel electrodes are prone to oxidation and lose their good conductivity, and nickel paste shrinks during the firing process, causing MLCC warping and fracture.

[0005] Barium titanate (BaTiO3) is a lead-free piezoelectric ceramic material discovered in the early 20th century. It has excellent high dielectric, low loss characteristics, and excellent piezoelectric and ferroelectric properties. It is widely used in MLCC, PTC and other fields, becoming one of the raw materials for electronic ceramics and is known as the "pillar of the electronic ceramics industry." The earliest industrial preparation method for BaTiO3 powder is the solid phase method, which uses BaCO3 and TiO2 as raw materials. After ball milling to fully mix the raw materials, they are calcined at a temperature above 1000°C to synthesize BaTiO3 powder. The chemical equation for this process is:

[0006] BaCO3+TiO2→BaTiO3+CO2↑.

[0007] BaTiO3 is a consistent melting compound with a melting point of 1618°C, and its crystal structure will also change with the change of temperature. In the temperature range from 1460°C to the melting point, its crystal structure is a hexagonal system, which is a stable phase, and crystal growth must be carried out below 1460°C. When the temperature is between 130 and 1460°C, the crystal structure is a cubic phase system, at which time the BaTiO3 crystal structure has the highest symmetry, so there is no ferroelectricity and piezoelectricity; in the temperature range of 0 to 130°C, BaTiO3 undergoes a paraelectric-ferroelectric phase transition, the crystal symmetry decreases, and it changes from a cubic system to a tetragonal system with ferroelectricity, at which time its ferroelectric and dielectric properties are the best; at -90 to 0°C, it changes to an orthorhombic system (monoclinic system), and the ferroelectricity does not disappear; when the temperature drops below -90°C, the BaTiO3 crystal structure changes to a trigonal system. Under normal circumstances, the room temperature dielectric constant of BaTiO3 ceramics is about 2400; when the temperature reaches the Curie point of BaTiO3, its dielectric constant will increase rapidly to about 10000. This characteristic of BaTiO3, coupled with its inherent high dielectric constant and low dielectric loss, makes it the preferred dielectric material in MLCC manufacturing.

[0008] Coating a BaTiO3 ceramic layer on the surface of Ni powder can effectively improve its sintering performance and antioxidant properties. First, the introduction of pure BaTiO3 ceramic coating material can avoid the incorporation of other substances besides the core material components of MLCC, and will not have an adverse effect on the internal electrode slurry and the performance of MLCC products; secondly, the BaTiO3 ceramic coating layer can improve the compatibility of the Ni electrode with the BaTiO3 ceramic dielectric layer during the sintering process, and improve the reliability of MLCC. The current preparation method of BaTiO3-coated Ni powder focuses on the liquid phase method, and the BaTiO3 coating layer is prepared by chemical reaction. Patent CN101774028A relates to BaTiO3-coated Ni powder and its preparation method. This invention uses ultrasonic spray thermal decomposition to prepare composite powder. This method belongs to the chemical method. The addition of more chemical substances during the preparation process may have a negative impact on the subsequent slurry preparation. In addition, this method also has problems such as poor sphericity of the composite powder.

[0009] Patent CN103508736A relates to BaTiO3 coated Ni powder and its preparation method. This invention adopts chemical hydrothermal crystallization method to prepare composite powder, and the sintering performance and anti-oxidation performance of powder product are improved to a certain extent. In the process of preparing single oxide (Cr2O3, or TiO2, or ZrO2) coated Ni powder by physical vapor phase method, the raw material is single, the process is simple and easy to control, and only the composition ratio between single oxide and Ni raw material is involved. However, in the coating process of multi-oxide system, there are melting, decomposition, evaporation of multiple oxide raw materials, and co-evaporation of Ni metal raw materials. The difference in evaporation rate of different raw materials makes it difficult to control the composition of powder product, and the composition, crystal structure and thickness of coating layer are difficult to control. These problems are solved in the present invention.

[0010] The DC arc plasma method is a physical vapor phase method for preparing core-shell type micro-nano composite powder materials. Its advantages are that it uses bulk raw materials, can be prepared on a large scale, has no chemical pollution, and is easy to control power and preparation atmosphere. Patent CN118847991 uses the DC arc plasma co-evaporation method to prepare core-shell BaTiO3 coated Ni powder materials in situ. On the basis of single oxide coated metal micro-nano powders, it further develops the preparation technology of multi-oxide ceramic material coated metal particles, realizes the preparation of complex oxide coated metal particles and their structural control. Compared with the conventional chemical solution method, it has the advantages of in-situ coating, rich raw material sources, high sphericity of powder products, no by-products, no chemical pollution, and easy scale-up.

[0011] However, in actual applications, it was found that whether the composite powder prepared by the hydrothermal crystallization method or the in-situ coated powder prepared by the DC plasma method, problems such as easy peeling of the coating shell, uneven coating, and loose bonding between the coating layer and nickel would occur. During the use of the slurry, there are still problems such as poor co-firing and warping. Summary of the invention

[0012] The purpose of the present invention is to provide a barium titanate coated nickel powder and slurry to solve the problem of the shrinkage rate of the inner electrode nickel powder and the ceramic dielectric mismatch during the co-sintering process of the MLCC metal inner electrode and the ceramic dielectric layer, and to provide a double-shell structure powder of barium titanate coated nickel powder, by arranging an inner shell of an oxygen compound and / or a sulfur compound on the surface of the nickel powder, and then arranging a barium titanate outer shell on the outer layer of the inner shell, the inner shell and the inner core, and the inner shell and the outer shell are tightly bonded respectively, the bonding force between the inner core and the outer shell is improved through the transition of the inner shell, and the stability of the nickel in the inner electrode slurry during the firing process is improved.

[0013] To achieve the above objectives, this application is implemented through the following technical solutions:

[0014] A barium titanate-coated nickel powder comprises a nickel powder core with a specific surface area equivalent particle size d of 30-600 nm; the surface thereof has a double-shell structure, the inner shell layer is an oxygen compound and / or a sulfur compound, and the outer shell layer is barium titanate; the inner shell layer has an average thickness of 1-25 nm, and the outer shell layer has an average thickness of 0.5-12.5 nm.

[0015] Furthermore, the outer shell layer is one of the discontinuously distributed porous, dot-shaped, and island-shaped barium titanate coatings.

[0016] Furthermore, the proportion of the barium titanate in the outer shell layer coating the inner shell layer surface is greater than 50%.

[0017] Furthermore, in the inner shell layer, the oxygen compound and / or sulfur compound is at least one of nickel oxide, nickel sulfide, nickel hydroxide and nickel carbonate.

[0018] Furthermore, the barium titanate-coated nickel powder has a discrete distribution, and according to the discreteness meter R=Dmax-Dmin>d, the Dmax is the particle size of the largest particle in the same field of view of its SEM photo counting no less than 10,000 particles, and Dmin is the particle size of the smallest particle in the same field of view.

[0019] A barium titanate-coated nickel powder slurry comprises any of the above-mentioned barium titanate-coated nickel powders.

[0020] Furthermore, the nickel content in the barium titanate-coated nickel slurry is 35-95%.

[0021] The beneficial effects of the present invention are:

[0022] The barium titanate-coated nickel powder involved in the present invention has a double-shell structure. In addition to improving the co-firing property of the nickel powder and the dielectric material through the barium titanate shell of the outer shell, the bonding degree between the nickel and the dielectric material can be better improved through the oxygen compound and / or sulfur compound of the inner shell, so as to improve the yield rate of the nickel powder and the dielectric material in the process of preparing electronic components and improve the electrical performance of the electronic components. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM photo of the barium titanate-coated nickel powder of the present invention.

[0024] Figure 2 This is a proportional TEM photo of the surface of the inner shell layer coated with barium titanate of the outer shell layer of Example 2.

[0025] Figure 3 This is a SEM photo of the surface ratio of the inner shell layer coated with barium titanate in the outer shell of Example 3.

[0026] Figure 4 This is the SEM photo of the barium titanate-coated nickel powder of Example 4.

[0027] Figure 5 This is the SEM photo of barium titanate-coated nickel powder in comparative example 1.

[0028] Figure 6 This is the SEM photo of barium titanate-coated nickel powder in comparative example 2. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is described in detail below through examples. The following examples are merely exemplary and can only be used to explain and illustrate the technical solution of the present invention, but cannot be construed as limiting the technical solution of the present invention.

[0030] The present application discloses a barium titanate-coated nickel powder, which has a nickel powder core with a specific surface area equivalent particle size d of 30 to 600 nm; its surface has a double shell structure, the inner shell layer is an oxygen compound and / or a sulfur compound, and the outer shell layer is barium titanate; the average thickness of the inner shell layer is 1 to 25 nm, and the average thickness of the outer shell layer is 0.5 to 12.5 nm.

[0031] In the present application, the outer shell layer is one of the discontinuously distributed porous, dot-shaped, and island-shaped barium titanate coatings.

[0032] In the present application, the proportion of the barium titanate of the outer shell layer covering the surface of the inner shell layer is greater than 50%.

[0033] In the present application, in the inner shell layer, the oxygen compound and / or sulfur compound is at least one of nickel oxide, nickel sulfide, nickel hydroxide, and nickel carbonate.

[0034] In the present application, the barium titanate coated nickel powder has a discrete distribution, according to the discreteness meter R=Dmax-Dmin>d, wherein Dmax is the particle size of the largest particle in the same field of view of its SEM photo with a count of not less than 10,000 particles, and Dmin is the particle size of the smallest particle in the same field of view. The nickel powder distributed in this way can have a better packing density in the slurry, forming more point contacts between spheres, thereby providing a better sintered body and conductive points.

[0035] The present application also discloses a barium titanate coated slurry, the nickel content of which is 35-95%.

[0036] Example 1

[0037] A barium titanate coated nickel powder has a specific surface area equivalent particle size d of 265nm; its surface has a double shell structure, the inner shell is oxide, XPS test shows that the oxide includes NiO and NI-CO, and the outer shell is barium titanate; the average thickness of the inner shell is 14nm, and the average thickness of the outer shell is 2.5nm. According to the discreteness meter R=D(max)-D(min), Dmax is the largest particle in the same field of view with a SEM photo count of not less than 10,000 particles, and its particle size is 1105nm, and Dmin is the smallest particle in the same field of view, and its particle size is 42nm. Figure 1 shown.

[0038] Example 2

[0039] A barium titanate coated nickel powder, having a nickel powder core with a specific surface area equivalent particle size d of 53nm; its surface has a double shell structure, the inner shell layer is a mixed layer of oxides and sulfides, and according to XPS testing, the oxides and sulfides include NiO, Ni(OH)2 and NiS, and the outer shell is barium titanate; the average thickness of the inner shell is 3nm, and the average thickness of the outer shell is 1.5nm. Furthermore, the outer shell layer is a discontinuously distributed island-shaped barium titanate coating, and the barium titanate coating of the outer shell layer accounts for 52% of the inner shell surface. From the structure, it can be seen that part of the inner shell is exposed. Figure 2 shown.

[0040] Example 3

[0041] A barium titanate coated nickel powder has a nickel powder core with a specific surface area equivalent particle size d of 546nm; its surface has a double shell structure, the inner shell is an oxide, and according to XPS testing, the oxide includes NiO, Ni(OH)2 and NI-CO, and the outer shell is barium titanate; the average thickness of the inner shell is 24nm, and the average thickness of the outer shell is 12nm. The outer shell is a non-continuously distributed porous barium titanate coating, and the proportion of the barium titanate coating on the outer shell surface is 97%. Figure 3 shown.

[0042] Example 4

[0043] A barium titanate coated nickel slurry, wherein the barium titanate coated nickel powder used has a nickel content of 65%. It has a nickel powder core with a specific surface area equivalent particle size d of 125 nm; its surface has a double shell structure, the inner shell is sulfide, and according to XPS testing, the sulfide includes NiS, and the outer shell is barium titanate; the inner shell has an average thickness of 6 nm, and the outer shell has an average thickness of 3 nm. Figure 4 shown.

[0044] Comparative Example 1

[0045] A barium titanate coated nickel powder has a nickel powder core with a specific surface area equivalent particle size d of 312 nm; the surface of the nickel powder has a shell layer of oxide coating, and according to XPS testing, the oxide includes NiO, Ni(OH)2 and NI-CO, and the shell thickness is 11 nm on average. Figure 5 shown.

[0046] Comparative Example 2

[0047] A barium titanate coated nickel powder, comprising a nickel powder core with a specific surface area equivalent particle size d of 347; and a barium titanate coating layer on the surface thereof, such as Figure 6 shown.

[0048] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A barium titanate coated nickel powder, characterized in that: A nickel powder core having a specific surface area equivalent particle size d of 30 to 600 nm; Its surface has a double shell structure, the inner shell layer is an oxygen compound and / or a sulfur compound, and the outer shell layer is barium titanate; the average thickness of the inner shell layer is 1-25 nm, and the average thickness of the outer shell layer is 0.5-12.5 nm.

2. The barium titanate-coated nickel powder according to claim 1, characterized in that: The outer shell layer is one of the discontinuously distributed porous, dot-shaped and island-shaped barium titanate coatings.

3. The barium titanate-coated nickel powder according to claim 1, characterized in that: The proportion of the barium titanate coating the inner shell surface in the outer shell is greater than 50%.

4. The barium titanate-coated nickel powder according to claim 1, characterized in that: In the inner shell layer, the oxygen compound and / or sulfur compound is at least one of nickel oxide, nickel sulfide, nickel hydroxide and nickel carbonate.

5. The barium titanate-coated nickel powder according to claim 1, characterized in that: The barium titanate coated nickel powder has a discrete distribution, and according to the discreteness meter R=Dmax-Dmin>d, the Dmax is the particle size of the largest particle in the same field of view of its SEM photo counting no less than 10,000 particles, and Dmin is the particle size of the smallest particle in the same field of view.

6. A barium titanate coated nickel slurry, characterized in that: The barium titanate-coated nickel powder comprises the barium titanate-coated nickel powder according to any one of claims 1 to 5.

7. The barium titanate coated nickel slurry according to claim 6, characterized in that: The nickel content in the barium titanate coated nickel slurry is 35-95%.

Citation Information

Patent Citations

  • Method for preparing Ni-BaTiO3 compound powder

    CN101774028A

  • Barium titanate coated nanometer nickel powder for inner electrode of MLCC (Multilayer Ceramic Capacitor) and preparation method thereof

    CN103508736A